2021
DOI: 10.1021/acs.macromol.1c02061
|View full text |Cite
|
Sign up to set email alerts
|

Hydrolysis-Induced Self-Assembly of High-χ–Low-N Bottlebrush Copolymers

Abstract: Densely grafted bottlebrush statistical copolymers (BSCPs) and bottlebrush block copolymers (BBCPs) were synthesized with polystyrene (PS) and poly­(solketal methacrylate) (PSM) side chains grafted to a polynorbornene backbone. The PSM chains could be hydrolyzed into poly­(glycerol monomethacrylate) (PGM), significantly increasing the segmental interaction parameter (χ). Self-assembly of the polymers was studied with small-angle X-ray scattering before and after hydrolysis. The well-known rapid self-assembly o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 74 publications
1
11
0
Order By: Relevance
“…However, the self-assembly of high-χ bottlebrush block copolymers in thin films suffers the same low-mobility issue we previously observed in bulk self-assembly. 64 The contorted lamellae with large curvatures as shown in Figure 6b indicate that the high-χ bottlebrush copolymers are trapped in an energetically unfavorable state due to the high energy barrier for different blocks to interpenetrate through each other and evolve into better lateral order. Low mobility of high-χ copolymers, especially bottlebrush copolymers, remains a major obstacle to obtain perfectly ordered arrays and guarantees further studies.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the self-assembly of high-χ bottlebrush block copolymers in thin films suffers the same low-mobility issue we previously observed in bulk self-assembly. 64 The contorted lamellae with large curvatures as shown in Figure 6b indicate that the high-χ bottlebrush copolymers are trapped in an energetically unfavorable state due to the high energy barrier for different blocks to interpenetrate through each other and evolve into better lateral order. Low mobility of high-χ copolymers, especially bottlebrush copolymers, remains a major obstacle to obtain perfectly ordered arrays and guarantees further studies.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The block copolymers were synthesized using a previously developed synthesis route. 55,64 Kapton tape for transmission X-ray scattering measurements was purchased from Fisher Scientific. Silicon wafers were purchased from International Wafer Service, Inc. (IWS).…”
Section: ■ Conclusionmentioning
confidence: 99%
“…As an example, Yu et al have demonstrated the use of BCPs containing a block with hydrolyzable functional groups to enhance the incompatibility between the blocks in situ, in order to drive the formation of small domain spacings for patterning applications in solid systems (both bulk and thin films). [73][74][75]92 In these works, a solketal functionality is used to increase χ after acid hydrolysis to form glycerol functional groups. Specifically, a lamella-forming poly(solketal methacrylate)-block-polystyrene (PSM-b-PS) BCP was synthesized with controlled molecular weights through RAFT polymerization.…”
Section: Reacting Polymer Template Hypercrosslinking Of Polystyrene B...mentioning
confidence: 99%
“…Living ring-opening metathesis polymerization (ROMP) represents a highly efficient and versatile approach to polymers with low-dispersity, tuneable topology, and diverse functions. , The third-generation Grubbs catalyst exhibited many attractive features including fast initiation, extremely rapid chain propagation, greatly suppressed chain transfer, and chain termination reactions. , Recently, Xia and Grubbs et al reported that narrowly dispersed diblock bottlebrush block copolymers (BBCPs) could be synthesized via grafting-through methods using living ROMP . Compared to their linear analogues, BBCPs show highly extended molecular backbones due to steric repulsions among the densely grafted polymeric side chains, resulting in greatly reduced intermolecular chain entanglements, , rapid self-assembly kinetics, and large nanostructures with tuneable photonic band gaps. Watkins group demonstrated the design and synthesis of amphiphilic diblock BBCPs using living ROMP, which were employed as the templates for directed self-assembly of functional nanoparticles into long-range ordered hybrid materials with advanced optical properties. ,, Other research groups (Rzayev, Wooley, Lodge et al) also reported the synthesis of triblock BBCPs for creation of nanostructured material through phase separation or well-controlled micellization in aqueous solutions. However, the synthesis of multiblock bottlebrush copolymers (MBBCPs) remained scarce, and only limited sequences and a few blocks of no more than five were reported. It is worth noting that tailing, shoulders, and broad dispersity (PDI >1.2) were usually observed in GPC curves of the obtained MBBCPs due to incomplete reinitiation of the resting Ru species. , For the synthetic procedure of sequential ROMP, a complete conversion of the first macromonomer (MM) is necessary before the addition of the second one to obtain MBBCPs with well-defined sequences. In this case, the death of catalytic species usually occur in a couple of hours through self-decomposition or because of bimolecular coupling under the monomer-absent condition. ,, Previous studies have mainly focused on acceleration of the polymerization rate by changing molecular structure of the MM, such as anchor groups, , stereochemistry, , and MW. , However, a long lif...…”
Section: Introductionmentioning
confidence: 99%